The Use of Photo-Essay to Report Advances in Applied Science and Health - Macnab, Andrew John; Mukisa, Ronald; Stothers, Lynn (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: In the applied health and science disciples there is an expectation that project work is reported through a publication. The conventional papers written to do this follow a structure that includes sections providing background, methods, results and a discussion or conclusion, supported by figures and tables. Sometimes photographs are included, and with more on line publications the opportunities have increased for these to be available in full color. Borrowing from the field of photojournalism photo-essays are now a publication option where a series of images are used to tell the story; these are often related to health and well-being.Aims: To summarize the methodology used to effectively combine a series of images with a brief text, and short reference list to create a visually engaging and informative short report.Guidelines: Images are taken throughout the project with consent obtained from those whose images will be recognisable. Creative licence is used to compile representative images into a sequence that conveys the background, method, results and outcome(s) of the project. Images need to be of high resolution; editing for light, colour and contrast, and cropping is allowed to increase their clarity and relevance. The ethics of photojournalism apply making inappropriate manipulation of images or erroneous captions unacceptable.Conclusion: Photo-essays are a novel and informative way to report on an applied health, social or scientific topic. The format is an excellent one to use for a brief report, or to prepare a research presentation for a scientific meeting. Received: 13 May 2018, Reviewed: 08 June 2018, Received: in revised form 27 June 2018, Accepted: 29 June 2018 DOI: https://doi.org/10.35898/ghmj-22199